Crusted Scabies: A Cause of Erythroderma to Remember - Gonçalves Ferreira, Iago; Lurdes Bueno, Jéssica; Dupont, Letícia; Luzzatto, Laura; Pereira Duquia, Rodrigo (Portuguese Journal Internal Medicine, 2023)
Crusted scabies or Norwegian scabies is a severe and highly contagious clinical variant of infestation by Sarcoptes scabiei, which can evolve exuberantly, coursing with diffuse erythroderma, which makes etiological diagnosis difficult, especially by non-dermatologists. Thus, the authors present a case report of erythroderma in a 65-year-old woman, who developed intense pruritus associated with erythroderma for about 2 weeks, with an associated fever peak. She had a previous clinical history of psoriasis and psoriatic arthritis, with long-term use of immunosuppressants and systemic corticosteroids. Evaluated by dermatologists who, through direct examination by skin scraping and skin biopsy, confirmed the diagnosis of crusted scabies. Based on this case report, the importance of differential diagnoses of erythroderma is highlighted, especially crusted scabies, a rare dermatosis that most often affects immunocompromised, frail, institutionalized patients or patients with precarious social conditions.